Role of Complement System in Kidney Transplantation: Stepping From Animal Models to Clinical Application - Qi, Ruochen; Qin, Weijun (Frontiers in Immunology, 2022)
Kidney transplantation is a life-saving strategy for patients with end-stage renal diseases. Despite the advances in surgical techniques and immunosuppressive agents, the long-term graft survival remains a challenge. Growing evidence has shown that the complement system, part of the innate immune response, is involved in kidney transplantation. Novel insights highlighted the role of the locally produced and intracellular complement components in the development of inflammation and the alloreactive response in the kidney allograft. In the current review, we provide the updated understanding of the complement system in kidney transplantation. We will discuss the involvement of the different complement components in kidney ischemia–reperfusion injury, delayed graft function, allograft rejection, and chronic allograft injury. We will also introduce the existing and upcoming attempts to improve allograft outcomes in animal models and in the clinical setting by targeting the complement system.